The Impact of Paid Family Leave on the Timing of Infant Vaccinations - Agnitra Roy Choudhury; Solomon Polachek (Institute of Labor Economics (IZA), 2019)
Raising a new-born child involves not only financial resources, but also time investment from the parents. A time constraint can affect important decisions made by parents at the early stages of an infant's life. One form of investment that is particularly important is vaccinating an infant. We analyze the impact of time constraints on immunization of infants on time. To establish a causal relationship, we exploit California's implementation of Paid Parental Leave Program as a natural experiment. Using a nationally representative dataset from the National Immunization Survey, we find evidence that the policy reduced late vaccinations for children born to parents in California after the policy was implemented. We test for heterogeneous effects of the policy on different subgroups in the population. We find the policy had a stronger impact on families that are below the poverty line. We conduct a series of falsification tests and robustness checks to test the validity of the results. In addition, our results are robust to several placebo tests.
Keywords: D04; I12; I18; J18; 330; vaccination; paid parental leave; difference-in-difference; synthetic control method